Structure–activity relationships of dibenzoylhydrazines for the inhibition of P-glycoprotein-mediated quinidine transport. Issue 14 (15th July 2016) - Miyata, Ken-ichi; Nakagawa, Yoshiaki; Kimura, Yasuhisa; Ueda, Kazumitsu; Akamatsu, Miki
Graphical abstract: Summary of QSAR results, (A) A-ring: 3, 5-dimethyl derivatives, (B) A-ring: 2-Cl derivatives. Highlights: The inhibition of P-gp-mediated quinidine transport was evaluated. A classical QSAR analysis and docking simulation were performed. The hydrophobic factor was the most important for the inhibitory activities. Different substituent effects were obtained in two series of DBHs. Different substituent effects suggest the different binding modes of each series. Abstract: We previously demonstrated that dibenzoylhydrazines (DBHs) are not only P-glycoprotein (P-gp) substrates, but also inhibitors. In the present study, we evaluated the inhibition of P-gp-mediated quinidine transport by two series of DBHs and performed a classical QSAR analysis and docking simulation in order to investigate the mechanisms underlying P-gp substrate/inhibitor recognition. The results of the QSAR analysis identified the hydrophobic factor as the most important for inhibitory activities, while electronic and steric effects also influenced the activities. The different substituent effects observed in each series suggested the different binding modes of each series of DBHs, which was supported by the results of the docking simulation.